Patterns of pre-service mathematics teachers’ scaffolding shaped by students’ error diagnosis - Lusiana, Restu; Andari, Tri; Elvierayani, Rivatul Ridho; Huda, Syaiful (Journal on Mathematics Education, 2025)
Effective mathematics instruction requires teachers to diagnose students’ errors and provide scaffolding that is responsive to their learning needs. Yet, pre-service pre-service mathematics teachers (PMTs) frequently encounter challenges in identifying the nature of students’ mistakes and in designing appropriate instructional support. This study investigates the types of student errors diagnosed by pre-service pre-service mathematics teachers and the scaffolding patterns that emerge from their diagnostic practices. Adopting a qualitative descriptive approach, data were gathered through video analysis, microteaching, classroom practice, and in depth interviews. The analysis indicates that pre-service pre-service teachers recognized four major categories of student errors: conceptual misunderstandings, procedural inaccuracies, representational mistakes, and strategic misapplications. In addressing these errors, they employed four corresponding scaffolding patterns. Conceptual scaffolding supported students in reconstructing mathematical meaning, procedural scaffolding provided step-by-step guidance, strategic scaffolding encouraged evaluation of alternative approaches, and metacognitive scaffolding fostered reflection on reasoning and symbolic interpretation. These findings underscore scaffolding as a dynamic and adaptive practice shaped by teachers’ professional vision. The study contributes to mathematics teacher education by demonstrating how practice-based programs can strengthen pre-service pre-service teachers’ capacity to notice, diagnose, and respond to students’ thinking, thereby promoting more inclusive and meaningful mathematics learning. This research provides new insights into how pre-service teachers’ scaffolding practices, shaped by error diagnosis, can inform teacher education globally.